Encyclopedia of computer knowldege DTP course kit volume - II (with one CD) - Gupta Vikas (Dreamtech Press, NewDelhi, 2005)
Stats/Maths
UGC X PLAN (2005-2006)
ENGLISH
Keywords: Encyclopedia of computer knowldege DTP course kit volume - II (with one CD); Stats/Maths; Stats/Maths